Antidepressant efficacy of electroconvulsive therapy is associated with a reduction of the innate cellular immune activity in the cerebrospinal fluid in patients with depression. (4th July 2018) - Kranaster, Laura; Hoyer, Carolin; Aksay, Suna S.; Bumb, Jan Malte; Müller, Norbert; Zill, Peter; Schwarz, Markus J.; Sartorius, Alexander
Abstract: Objectives: A bidirectional link between the antidepressant effects of electroconvulsive therapy (ECT) and the modulation of the immune system has been proposed. To elucidate the interplay between antidepressant treatment and macrophage/microglia activation in humans, we performed a study on the effects of the antidepressant treatment by ECT on markers of macrophage/microglia activation in patients with depression. Methods: We measured six different markers (IL-6, neopterin, sCD14, sCD163 MIF and MCP1) of macrophage/microglia activation in the cerebrospinal fluid (CSF) and blood of 12 patients with a severe, treatment-resistant depressive episode before and after a course of ECT. Results: Some markers in the CSF of remitters were reduced after the ECT course and differed from non-remitters, but no differences were found before and after ECT independently from the antidepressant efficacy. CSF baseline levels of some markers could predict the reduction of depressive psychopathology during ECT. Higher CSF levels indicating increased macrophage/microglia activation at baseline predicted a better treatment response to ECT. Conclusions: Although the sample size was small, our data suggest that macrophages/microglia are involved in the pathophysiology of major depression and that antidepressant efficacy by ECT might be partly explained by the modulation of the innate immune system within the brain.